Language Development in 2-to-4-year-old Children with Cerebral Palsy - Hunia Kashif, Muhammad Azzam Khan, Zunaira Zulkarnain, Abeeha Fatima Mansoor, Bareera Saeed, Fahad Masood, Arslan Saleem Chugtai (Pakistan Journal of Medical & Health Sciences, 2022)
One of the frequently occurring disabilities of early age is Cerebral Palsy. Impairments in speech, language and communication usually co-occur with CP. These arise from the auditory, sensory and visual disorders that accompany CP. Delay or impairments in the development of language in cerebral palsy can lead to different speech and language disorders. Objectives: Evaluating the development of language in children with cerebral palsy between 2-4 years of age. Methods: A cross-sectional study design was utilized. Data was collected from different healthcare centers, clinics and hospitals. Convenient-based sampling technique was used. Children with co-morbid conditions with CP were not included in the study sample. The assessment tool used for evaluation of language development was ‘PORTAGE – early education program.’ The language related questions of PEEP were included as the tool for data collection. The data for 108 patients of cerebral palsy between 2-4 years of age was compiled. The results have been divided into demographics and the levels of portage i.e., 0-1 years, 1-2 years, 2-3 years and 3-4 years. The receptive as well as expressive language has been evaluated for these children. Total 70 questions have been added from the portage guide for up to 4 years of age. Results: It is observed that a little more than half of the patients included in the study experience varying degrees of language difficulties. These difficulties are an accumulation of receptive as well as expressive impairments. On the contrary, a little under half of the patients (46.38%) have language abilities developed according to their age. Early identification of language impairment in children with Cerebral Palsy can lead to early intervention. This study evaluates the language development in young patients with CP. The results reveal the percentage of patients with language impairments. Hence, the study encourages early evaluation and treatment of language disorders in this population. Conclusion: The most vital period of language development ranges till 5 years of age. So, 2-4 years is an important period of time for language development in an individual. An in-depth assessment of speech, language, cognitive and motor skills should be conducted during this time for CP children. Keywords: Cerebral Palsy, Portage Early Education Program, Language Development, Language Impairment.